Ritual Sesaji sebagai Representasi Ekologi Budaya pada Masyarakat Jawa - Kabelen, Marista Christina Shally; Kurniawati, Atik; Rusfadia Saktiyanti Jahja; Meila Riskia Fitri (Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2025)
This research explores the ritual offering culture in Java, particularly in Yogyakarta, highlighting its significance as a non-material aspect of Indonesian culture. Ritual offerings are a form of cultural expression that embodies local wisdom, reflecting gratitude towards ancestors and requests for blessings from nature and spiritual forces. Employing a qualitative approach, the study utilizes structured interviews and observations to gather insights into the practice and its evolution over time. The findings indicate that offerings serve as spiritual rituals and mechanisms for environmental adaptation and cultural identity preservation. They facilitate a harmonious relationship between humans and nature, reinforcing social bonds within the community. Furthermore, the research underscores the importance of local ecological knowledge in shaping the rituals, demonstrating how cultural practices adapt to environmental conditions. Ultimately, the ritual offering emerges as a vital practice that balances spiritual beliefs, environmental stewardship, and cultural sustainability, ensuring that the community's values and traditions are transmitted across generations.